Pandemic and its Discontents, An Opinion - Waqar, Mahmud (Journal of Current Viruses and Treatment Methodologies, 2020)
An opinion piece reflecting on the societal and scientific frictions revealed by the pandemic. It considers uncertainty, polarization, and the role of expertise, advocating resilient systems and transparent communication.
Keywords: COVID-19; SARS-Cov-2; mental health